ANALISIS ANCAMAN PHISHING DALAM LAYANAN ONLINE BANKING - Radiansyah, Ikhsan; Rusdjan, Candiwan; Priyadi, Yudi (Faculty of Economics and Business, University of Muhammadiyah Malang, 2016)
The purpose of this study was to determine the factors that cause the emergence of phishing and prevention against phishing threats. Systematic Literature Review methods used to find answers to the research questions by searching for studies related to the threat of phishing in online banking services and perform narrative synthesis on the findings. Minimal knowledge of the user, and the user's psychological privacy of users of social networking services considered as factors that cause phishing. Educating users about the threat of cyber crime, prevention at the level of e-mail, the use of anti-phishing software, and system implementation disposable password in banking services is an effective deterrent to the threat of phishing. Users must have a good knowledge of the threat of crime, especially phishing, and the Bank has the responsibility to provide education related to threats that can harm the user.